Elevated neutrophil extracellular trap levels in periodontitis: Implications for keratinization and barrier function in gingival epithelium - Cui, Ya‐yun; Yang, Yi‐heng; Zheng, Jia‐yi; Ma, Hui‐hui; Han, Xue; Liao, Chong‐shan; Zhou, Min (Journal of clinical periodontology, 2024)
Aim To explore the levels of neutrophil extracellular traps (NETs) in patients with periodontitis and examine their effects on keratinization, barrier function of human gingival keratinocytes (HGKs) and the associated mechanisms. Materials and Methods Saliva, gingival crevicular fluid (GCF), clinical periodontal parameters and gingival specimens were collected from 10 healthy control subjects and 10 patients with stage II–IV periodontitis to measure the NET levels. Subsequently, mRNA and protein levels of keratinization and barrier indicators, as well as intracellular calcium and epithelial barrier permeability, were analysed in HGKs after NET stimulation. Results The study showed that NET levels significantly elevated in patients with periodontitis, across multiple specimens including saliva, GCF and gingival tissues. Stimulation of HGKs with NETs resulted in a decrease in the expressions of involucrin, cytokeratin 10, zonula occludens 1 and E‐cadherin, along with decreased intracellular calcium levels and increased epithelial barrier permeability. Furthermore, the inhibition of keratinization by NETs is ERK‐KLF4‐dependent. Conclusions This study indicates that NETs impair the barrier function of HGKs and suppress keratinization through ERK/KLF4 axis. These findings provide potential targets for therapeutic approaches in periodontitis to address impaired gingival keratinization.